Pseudomonas fluorescens Complex and Its Intrinsic, Adaptive, and Acquired Antimicrobial Resistance Mechanisms in Pristine and Human-Impacted Sites - Myllena Pereira Silverio; Gabriela Bergiante Kraychete; Alexandre Soares Rosado; Raquel Regina Bonelli (MDPI AG, 2022)
Pseudomonas spp. are ubiquitous microorganisms that exhibit intrinsic and acquired resistance to many antimicrobial agents. Pseudomonas aeruginosa is the most studied species of this genus due to its clinical importance. In contrast, the Pseudomonas fluorescens complex consists of environmental and, in some cases, pathogenic opportunistic microorganisms. The records of antimicrobial-resistant P. fluorescens are quite scattered, which hinders the recognition of patterns. This review compiles published data on antimicrobial resistance in species belonging to the P. fluorescens complex, which were identified through phylogenomic analyses. Additionally, we explored the occurrence of clinically relevant antimicrobial resistance genes in the genomes of the respective species available in the NCBI database. Isolates were organized into two categories: strains isolated from pristine sites and strains isolated from human-impacted or metal-polluted sites. Our review revealed that many reported resistant phenotypes in this complex might be related to intrinsic features, whereas some of them might be ascribed to adaptive mechanisms such as colistin resistance. Moreover, a few studies reported antimicrobial resistance genes (ARGs), mainly β-lactamases. In-silico analysis corroborated the low occurrence of transferable resistance mechanisms in this Pseudomonas complex. Both phenotypic and genotypic assays are necessary to gain insights into the evolutionary aspects of antimicrobial resistance in the P. fluorescens complex and the possible role of these ubiquitous species as reservoirs of clinically important and transmissible ARGs.